EFFECTIVENESS OF THE REVIEW OF PUBLIC PROCUREMENTS IN SELECTED COUNTRY - Linhartová, Veronika; Macháčková, Aneta (Varazdin Development and Entrepreneurship Agency, 2018)
Supervision and control of public procurement is a crucial topic as public funds are used on a considerable amount of money with a significant amount of money from public budgets. If the contracting authority favors one of the participants, this will have a negative impact on all the country's inhabitants. These phenomena must be avoided; therefore, the regulation and controls in this area are important and necessary from the point of view of the independent body. In the Czech Republic, this power is placed in the hands of the Office for the Protection of Competition. The aim of the paper is to determine how the contracting authorities react to significant fines imposed by the Office for the Protection of Competition. Also, if the fine imposed worked as a means of modifying the public procurement procedure and if there were new measures or a revision of the existing procedures adopted to avoid repeated violations of the Public Procurement Act. Based on research over the period 2013 to 2014, the effectiveness of the Office for the Protection of Competition supervision is not very high. The inefficiency stems primarily from the unwillingness to identify the responsible person who caused the breach of the law.
EFEKTIVNOST A ÚČINNOST PŘEZKUMU VEŘEJNÝCH ZAKÁZEK
Keywords: Public procurements; Office for the Protection of Competition; review process; Public Procurement Act; Czech Republic.; Veřejné zakázky; Úřad pro ochranu hospodářské soutěže; přezkumné řízení; Zákon o zadávání veřejných zakázek; Česká republika.